Breeding waterbird populations of the islands of the Northern Persian Gulf, Iran. - Tayefeh, Farhad Hosseini; Hussin, Mohamed Zakaria; Amini, Hamid; Ghasemi, Saber; Ghasemi, Meysam (2011)
In 2010, we estimated the breeding waterbird popula tions on the uninhabited islands of the northern Persian Gulf, some of the most important waterbird nesting sites in Southwest Asia. We also compared the 2010 census results with data from the 1970s. Over 120,000 breeding pairs of waterbirds of nine species were estimated on seven islands in 2010. The most abundant species were Bridled Tern Sterna anaethetus (74,113 pairs) and Lesser Crested Tern Sterna bengalensis (30,799 pairs). The results indicated that 20% of the global population of Crab Plover Dromas ardeola breed in the northern part of the Persian Gulf. The breeding population of White Cheeked Terns Sterna repressa had decreased by about 98% since the 1970s, while the populations of all the other species had increased. Further monitoring of the breeding waterbirds is needed in order to suggest appropriate measures for the conservation of these important waterbird populations. Compared with the situation in the 1970s, some islands are no longer suitable as nestingsites for waterbirds because of human exploitation, occupation by the military and development for the oil and gas industries.